1993
DOI: 10.1073/pnas.90.24.11965
|View full text |Cite
|
Sign up to set email alerts
|

Single photon emission computed tomographic imaging demonstrates loss of striatal dopamine transporters in Parkinson disease.

Abstract: ABSTRACT[123I][(lR)-2(3-carbomethoxy-3fl-(4-iodophenyl)tropane] ([123'IJ-CIT) labels dopamine transporters and is, therefore, a marker of neurons that degenerate in Parkinson disease. Single photon emission computed tomography imaging with [123I]P-CIT showed that radioactivity in striatal regions in healthy subjects increased during a 2-day imaging study, whereas that in Parkinsonian patients peaked earlier at reduced levels relative to healthy subjects. Kinetic analyses of radioactivity in plasma and brain su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
130
1
4

Year Published

1995
1995
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(140 citation statements)
references
References 17 publications
5
130
1
4
Order By: Relevance
“…It has been used in several studies to observe the changes in the density of dopamine transporter in human brain (Innis et al 1993;Brücke et al 1993;Kuikka et al 1993;Tiihonen et al 1995). b-CIT also MiniReview has affinity to the serotonin transporter (Boja et al 1994), which makes the interpretation of the analysis of radioactivity distribution difficult in brain areas possessing high density of both 5-HT-and dopamine transporters.…”
Section: Dopamine Transporter In Vivo Imagingmentioning
confidence: 99%
“…It has been used in several studies to observe the changes in the density of dopamine transporter in human brain (Innis et al 1993;Brücke et al 1993;Kuikka et al 1993;Tiihonen et al 1995). b-CIT also MiniReview has affinity to the serotonin transporter (Boja et al 1994), which makes the interpretation of the analysis of radioactivity distribution difficult in brain areas possessing high density of both 5-HT-and dopamine transporters.…”
Section: Dopamine Transporter In Vivo Imagingmentioning
confidence: 99%
“…[ 123 I]-2b-carbomethoxy-3b-(4-iodophenyl)tropane ([ 123 I]b-CIT) is a radiotracer with high affinity to monoamine transporters (Innis et al, 1991;Boja et al, 1992) and thus can be used to visualize the central serotonin (SERT) and dopamine transporters (DAT) of the human brain in vivo with single photon emission computed tomography (SPECT) (Innis et al, 1993;Kuikka et al, 1993;Brücke et al, 1993;Pirker et al, 2000). b-CIT has been shown to accumulate in distinct brain areas, primarily in striatal, diencephalic, midbrain, and brainstem regions (Innis et al, 1991;Laruelle et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In SPET studies using [ 123 I]2β-carbomethoxy-3β-(4-iodophenyl)tropane ([ 123 I]β-CIT), which has been shown to be sensitive to dopaminergic presynaptic degeneration [4], Van Dyck et al confirmed in 28 healthy subjects the post-mortem reports on DA transporter loss with increasing age [5].…”
Section: Introductionmentioning
confidence: 99%